077 Bezier-spline curves to describe the paediatric airway: a proof of concept project. (December 2018) - Morrison, C; Roberts, J; Adams, D; Miquel, M; Cunnington, P
Abstract : Introduction: The traditional teaching, that basic airway manoeuvres align the three airway axes of mouth, pharynx and larynx, has been disproved in adults using MRI. An alternative model of airway management has been proposed, considering the airway not as axes but as two curves; a primary (oropharyngeal) and a secondary (pharyngo-glotto-tracheal) on each side of an inflection point (PI). 1 This has been defined using four anatomical landmarks; tip of incisors, hard and soft palate junction, tip of epiglottis and mid-trachea at the level of the 7th cervical vertebra. The aim of this study was to establish if this methodology could be applied to the paediatric airway, using MRI. Methods: Ten children who underwent sedated head/neck MRI were identified and anonymised. Mid-sagittal MR images were used for semi-automatic analysis using MATLAB (R2016a). A Bezier/spline curve was automatically generated and the user could adjust and add control points in order to model the primary and secondary curves. The software automatically calculated the line of sight (LoS), inflection point (PI), angle of inflection and the area between primary curve and LoS. Results: The methodology was successfully applied in children. However, it was often difficult to define the curves using the adult anatomical landmarks, due to the soft tissues of the paediatric airway sitting in close proximity. In the mid-sagittal plane, the large tongue, cephalad larynx and elevated epiglottis can result in the absence of an apparent clear airway. In those cases, applying the fixed four anatomical points lead to curves with additional curvatures. Discussion: New thinking is required to establish which anatomical landmarks should be used in this population to reproduce the two curves. Reference: Greenland KB, et al. British Journal of Anaesthesia2010;105(5):683–90.